Questioning Strategies Applied by Lecturers in EFL Class - Rizkariani Sulaiman (Linguistics Initiative, 2021)
The purpose of this study is aimed at finding out the questioning strategies used by lecturers during teaching, the types of questions, and the reasons for using these questioning strategies in classroom interactions in the English Education Study Program. The sample in this study are three lecturers at the English Education Study Program, Faculty of Letters, Indonesian Muslim University. The sample is selected based on teaching experience and has obtained an Educator Certificate. Then, this study uses a descriptive qualitative approach, especially discourse/conversation analysis. Data collection is carried out in three stages, namely knowing the schedule, observing the online lectures, and interviewing. Furthermore, the data is analyzed into three stages, namely data reduction, data presentation, and drawing conclusions. Based on the description of the results and discussion, it can be concluded as follows: The questioning strategies applied by the lecturers are: (1) opening questions; (2) rhetorical questions; (3) managerial questions; (4) knowledge questions; (5) comprehension/understanding questions; (6) questions about specific information; (7) analysis questions; (8) use of pausing strategy; (9) the use of prompting strategies; (10) use of probing and prompting strategies; (11) application questions; and (12) closed questions. The purpose of the application of the questions: (1) regulate the flow/process from the beginning (apperception) to reinforcement and review at the end of the lecture; (2) provide a stimulus so that students think critically; (2) directing the student's flow of thought to focus on the discussion; (3) giving emphasis, affirmation, examples; (4) knowing the level of understanding of students in the cognitive domain from C1, C2, C3 and C4; (5) build emotional relationship with students; (6) the questions are presented using pausing, prompting and probing techniques to guide and direct students to find complete answers and equal opportunities for all students to provide responses.